Republic of Kazakhstan : 2009 Article IV Consultation; Staff Report; Supplement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Kazakhstan's financial system remains highly stressed despite large-scale government support; the economy is expected to contract in the near future. The staff report for Kazakhstan's 2009 Article IV Consultation discusses economic developments and policies. Kazakhstan is better placed than many emerging market economies to weather the crisis given its large official foreign currency assets, low public debt, and favorable medium-term prospects. A full and independent assessment of all systemically important banks should be carried out in tandem with the strengthening of regulation and supervision, and the improvement of corporate governance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet